Anti‐consumer ethics: What consumers will not do for ethical reasons. (8th January 2021) - Muncy, James A.; Iyer, Rajesh
Abstract: The exploratory study examines the intersection of anti‐consumption and consumer ethics. It focuses on categories of products and services that consumers refuse to consume for moral or ethical reasons. We asked 292 respondents to indicate a product or service that they choose not to buy for ethical or moral reasons and what those reasons are. Harm was a significant determinant of these consumer's decisions not to buy. Reasons tended to be more of a micro, individualistic nature and usually did not reflect macro, societal level concerns. These results suggest that consumers are interested more in avoiding unethical behavior than in shopping for a better world. Managers should, therefore, make sure that their products are not seen as unethical.